The job guarantee: toward true full employment (Basingstoke, 2013)
"This timely collection will be the first of its kind to focus on the practical application of the government job guarantee (JG) for both developed and developing economies. Global case studies include: United States, China, Ghana, Argentina, Ireland, Iceland, and India."